138k views
0 votes
Which step was the first error made? -3\left(2x-3\right)=33−3(2x−3)=33 -6x+6=33−6x+6=33 step 1 -6x=27−6x=27 step 2 \frac{\left(-6x\right)}{-6}=\frac{\left(27\right)}{-6} −6 (−6x) ​ = −6 (27) ​ step 3 x=-4.5x=−4.5 step 4 Step 3 Step 2 Step 1

1 Answer

1 vote

Given:

The equation is


-3(2x-3)=33

The incorrect solution steps are given.

To find:

The first error.

Solution:

We have,


-3(2x-3)=33

Using distributive property, we get


-3(2x)-3(-3)=33


-6x+9=33

The given step 1 is
-6x+6=33, which is not correct.

Therefore, there is first error in step 1 because the distribution property is not used properly.

Hence, the correct option is D.

User Franz Gastring
by
5.0k points